2008
DOI: 10.1093/ajcn/88.1.224
|View full text |Cite
|
Sign up to set email alerts
|

Tea consumption and cognitive impairment and decline in older Chinese adults

Abstract: Regular tea consumption was associated with lower risks of cognitive impairment and decline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
179
2
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(197 citation statements)
references
References 31 publications
14
179
2
2
Order By: Relevance
“…It has been found that green tea consumption is significantly associated with a lower risk of mortality due to stroke [29] and pneumonia [30] and imparts a lower risk of cognitive impairment [31], depression [32], and psychological distress [33]. These results have been confirmed by other researchers [34][35][36][37]. In addition, other epidemiologic studies have indicated that green tea consumption is associated with a lower risk of osteoporosis [38,39], and randomized placebo-controlled trials have indicated that green tea is effective in lowering cardiovascular risk factors [40,41].…”
Section: The Health Effects Of Green Teasupporting
confidence: 61%
“…It has been found that green tea consumption is significantly associated with a lower risk of mortality due to stroke [29] and pneumonia [30] and imparts a lower risk of cognitive impairment [31], depression [32], and psychological distress [33]. These results have been confirmed by other researchers [34][35][36][37]. In addition, other epidemiologic studies have indicated that green tea consumption is associated with a lower risk of osteoporosis [38,39], and randomized placebo-controlled trials have indicated that green tea is effective in lowering cardiovascular risk factors [40,41].…”
Section: The Health Effects Of Green Teasupporting
confidence: 61%
“…In addition, two studies had combined coffee and tea drinking as caffeine intake and indicated some positive effects on cognitive functioning [15,16]. For tea consumption, only one study has found positive effects against cognitive decline [19].…”
Section: Discussionmentioning
confidence: 99%
“…In the Singapore Longitudinal Ageing Studies (SLAS) cohort among 55 years old persons, regular tea drinking was associated with a reduced risk of cognitive decline during a 1-2 year period [19].…”
Section: Previous Longitudinal Studiesmentioning
confidence: 99%
“…Comparable results were obtained in another study including 2501 Chinese aged 455 years. 5 The authors showed by similar methods that the intake of green tea is significantly related to a lower prevalence of cognitive impairment. Taken together, there is preliminary evidence in the literature that the intake of green tea or its main ingredients have a positive impact on cognitive functions.…”
Section: Introductionmentioning
confidence: 99%